Kemampuan Pemecahan Masalah Matematis Siswa dalam Menyelesaikan Soal Cerita Program Linier Ditinjau dari Minat Belajar di Kelas XI SMA Negeri 01 Menjalin - Hermawati, Wiwin; Ardiawan, Yadi; Irvandi, Wandra (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The influence of interest on student learning is quite large, because it also indirectly affects the talents they have. The purpose of this study is to describe students' problem-solving abilities as viewed from the students' learning interests themselves. The method used is a qualitative descriptive method. This study was conducted at SMA Negeri 01 Menjalin with 29 students as research subjects and six students taken from high, medium, and low learning interests. The data collection tools used were problem-solving ability test sheets, learning interest questionnaires, and validation sheets. Meanwhile, the data collection techniques used were direct communication techniques and measurement techniques. Data reduction, data presentation, and drawing conclusions are some of the data analysis approaches used in this study. The results of this study indicate that students with high learning tendencies also tend to be skilled in solving problems. There are six students who have high learning tendencies; five of them are very good at solving problems, and one is fine. Even students who are not very interested in school can have impressive problem-solving abilities. Of the thirteen students with a high learning propensity, seven showed outstanding problem-solving skills